2015
DOI: 10.4000/emscat.2510
|View full text |Cite
|
Sign up to set email alerts
|

Diseases and their origins in the traditional worldview of Buryats : folk medicine methods

Abstract: La nature des maladies dans les perceptions traditionnelles des peuples mongols est un phénomène peu étudié qui nécessite une étude approfondie. Dans les croyances des gens de culture traditionnelle toute maladie est considérée comme un écart par rapport à une norme. C’est une mauvaise conséquence d’une perturbation humaine de l’ordre des interactions entre le monde des hommes et le monde des divinités et des esprits, et, comme tel, il est inscrit dans la langue. Traiter une maladie consistait en une « correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…It has retained its empirical characteristics and have never been adopted into neighbouring countries (Dagvatseren, 1989). Other scientists also conclude that baria zasal of concussion is the only treatment available in Mongolia (Bold, 1989;Dagvatseren, 1989;Dolgormaa, 1990;Sodnompilova & Bashkuev, 2015;Tsybikova et al, 2019). Scientists also found that the uniqueness of Mongolian baria zasal for concussion from other folk medicines.…”
Section: Concussion Treatment Through Baria Zasalmentioning
confidence: 99%
See 2 more Smart Citations
“…It has retained its empirical characteristics and have never been adopted into neighbouring countries (Dagvatseren, 1989). Other scientists also conclude that baria zasal of concussion is the only treatment available in Mongolia (Bold, 1989;Dagvatseren, 1989;Dolgormaa, 1990;Sodnompilova & Bashkuev, 2015;Tsybikova et al, 2019). Scientists also found that the uniqueness of Mongolian baria zasal for concussion from other folk medicines.…”
Section: Concussion Treatment Through Baria Zasalmentioning
confidence: 99%
“…Scientists also found that the uniqueness of Mongolian baria zasal for concussion from other folk medicines. For instance, in Tibetan medicine, which is quite similar to TMM, practitioners use calm methods to treat concussion while Mongolians use a kind of vibration (shaking head) in combination with massage for the treatment (Bold, 1989;Sodnompilova & Bashkuev, 2015). In other words, some Bariachis believe that concussion can be treated by shaking the head forward and backwards.…”
Section: Concussion Treatment Through Baria Zasalmentioning
confidence: 99%
See 1 more Smart Citation
“…Для них очищающей силой обладал огонь, а вода принадлежала к хтоническому миру, обозначала черный, плохой цвет и была окружена множеством табу [Stolpe 2008: 66-67]. Например, запрещалось наливать воду в молоко, брызгать водой в огонь, ходить за водой в ночное время (растревоженные водяные духи нашлют болезнь) [Sodnompilova, Bashkuev 2015].…”
Section: глава IIIunclassified
“…В монгольском понимании очищающей силой обладал огонь, а вода, напротив, имела отрицательное значение, относясь к хтоническому миру и обозначая черный, плохой цвет [Stolpe 2008: 66-67]. С ней было связано множество табу: от запрета наливать воду в молоко и брызгать ей в огонь до табу на хождение за водой в ночное время (растревоженные водные духи нашлют болезнь) [Sodnompilova, Bashkuev 2015]. the religious worldview and indigenous medical systems, such as folk medicine and Tibetan medicine.…”
unclassified